A hedonic price analysis for the Portuguese wine market: Does the distribution channel matter?. Issue 1 (1st January 2019) - Rebelo, João; Lourenço-Gomes, Lina; Gonçalves, Tânia; Caldas, José
ABSTRACT: Price is a core component of both wine firms' and consumers' decision-making and so there has been a lot of analysis of the determinants of wine price. Most of the research has used the hedonic price function and assumed that the wine market is homogeneous with respect to both distribution channel and price segments. In this paper, a hedonic price function is estimated using data from a specialist retailer and a large supermarket, i.e., retailers in two different consumer market segments, niche and mass market, respectively. We conclude that the wine market is heterogeneous, and the importance of the various price determinants differs between distribution channels and, in the case of the specialist retailer, throughout the conditional statistical distribution of the price. This result may help the wine companies to place themselves in the market value chain.